DETERMINATION OF THE QUANTITATIVE COMPOSITION OF MINERAL SUBSTANCES IN THE SKIN (Scientific journal of the Fergana State University, 2023)
In this article, determination of mineral substance (ash) content of domestic animal skins in Fergana Valley. Quantitative indicators of s, p, d, f-family elements present in the periodic system of elements in animal skin were determined. The amount of с elements is 51.2-82.83% of the total skin mass, p elements are 16.85-30.14%, and d and f elements are present in minimal amounts. These elements are part of animal skin and provide their elasticity. These elements give hygienic properties, elasticity, and strength to products made from natural leather.